THE INFLUENCE OF DIGITAL MULTIMEDIA ON SOCIAL STUDIES LEARNING OUTCOMES OF THIRD-GRADE STUDENTS AT SDN 4 TELAGA, GORONTALO REGENCY - Mahmud, Yane Hardiyanti (LPPM STISIPOL Mujahiddin, 2025)
This study investigates the influence of digital multimedia on Social Studies learning outcomes of third-grade students at SDN 4 Telaga, Gorontalo Regency. The research employed a quantitative causal design with the entire population of 27 students as the sample. Data were collected through questionnaires and documentation, and analyzed using simple linear regression. The results of the study demonstrate that digital multimedia has a significant effect on student learning outcomes. The coefficient of determination (R²) was 0.492, indicating that 49.2% of the variance in learning outcomes can be explained by the application of digital multimedia. The remaining 51.8% is influenced by other factors, including students’ learning interest, instructional models, parental involvement, motivation, and the school environment. These findings highlight the importance of integrating digital multimedia into classroom practices to enhance students’ understanding and engagement in Social Studies learning. The use of multimedia can help overcome contextual and resource limitations, thereby supporting more effective teaching and improved learning outcomes.